Slope Environmental Lapse Rate (SELR) of Temperature in the Monsoon Regime of the Western Himalaya - Thayyen, Renoj J.; Dimri, Ashok P. (Frontiers in Environmental Science, 2018)
The interplay of moisture, temperature and precipitation forced through the orographic processes sustain and regulate the Himalayan cryospheric system. However, factors influencing the Slope Environmental Lapse Rate (SELR) of temperature along the Himalayan mountain slopes and an appropriate modeling solution remain as a key knowledge gaps. The present study evaulates the SELR variations in the monsoon regime of the western Himalaya and proposes a modeling solution for the valley scale SELR assessment. SELR of selected station pairs in the Sutlej and Beas basins ranging between the elevation of 662 m a.s.l. to 3130 m a.s.l. and that of Garhwal Himalaya between 770 m a.s.l. and 3820 m a.s.l. were assessed in this study. Results suggest that the moisture-temperature interplay is not only forcing the seasonal variations, but also the elevation - depended variability of the temperature SELR. Temperature lapse rate constrianed to the nival-glacier regime is found to be comparable to the saturated adiabatic lapse rate (SALR) and lower than the valley scale SELR. The study also suggests that the bi-modal pattern of the annual temperature lapse rates earlier observed in the Nepal Himalaya is extended up to upper Ganga, Sutlej and Beas basins in the western Himalaya. This seasonal variability of SELR is found to be closly linked with the seasonal variations in the lifting condensation levels (LCLs) over the region. Inter-annual variation in SELR of the nival-glacier regime are found to be significant while that of the valley scale SELR are more stable. We propose a simple preliminary but robust model for deriving the valley scale SELR of monsoon regime modifying the equation governing pseudo adiabatic lapse rate. The SELR modeling solution is achieved by deriving monthly SELR indices using the data of two station pairs in the Sutlej and Beas basins during the 1986-2005 period through K-fold cross validation. The model sucessfully captures seasonal SELR variations, and was tested compared to the station pairs in the upper Ganga basin as well and showed significant improvement over the standard environmental lapse rate of 6.5K/km.